PENGENTASAN PERILAKU AGRESI PESERTA DIDIK MELALUI LAYANAN BIMBINGAN KELOMPOK OLEH GURU BK DI SMP NEGERI 25 PADANG - Guciani, Sari - (Bimbingan dan Konseling, 2014)
Background of this research is studentâs behavior phenomenon in the school like brawl, figh that do by studentâs in the class, indecent behavior. Therefore, studentâs of result study is not good, do not success in Ujian Nasional (UN), etc. This problem identify teacherâs approaches are important to solve that problems through counseling approaches. Thatâs are: 1) removing studentâs aggression through group counseling, which can see from group counseling application. 2) removing studentâs behavior aggression through group counseling which can see from the advantages of group counseling. Design of this research is descriptive research. Means, describing of condition, facts, and reality in the field about removing of studentâs agression behavior through group counseling. There are 6 informant in this research. The informant divide into two categories are 2 counselor as core informant and 4 students as additional informant instrument of this research is interview. Technique of data collection is reduction of data, presenting the data, and taking of conclution. The result of this research shows that: 1) counselor did group counseling well to remove studentâs behavior agression. 2) the advantage of group counseling is there are changing studentâs behavior become good behavior, and studentâs feel happy to do group counseling. Refering to this research is recommended to counselors to avoid studentâs behavior agression through group counseling.